Trade Union in the Transnational Company - ЧеглаковаЛюдмила Михайловна (Journal of Economic Sociology, 2010)
The enterprises that are intergraded into the transnational corporations account for qualitative changes in the labour relations. How do the traditional practices of the trade union adapt to the policy and actions of the new owner? What problems stem from this interaction? Do the preferences and work formats of the trade union change in the organization? The author provides the answers to these questions by analyzing the experience of Samarkand metallurgical plant.